Evaluation of the Implementation of Electronic Medical Record Using the Pieces Approach to Support Satu Sehat in the Emergency Department - Sunargo, Bambang; Hartono, Budi; Samingan, Samingan (Poltekkes Kemenkes Jakarta III, 2025)
The application of Electronic Medical Records (EMR) has become an integral part of the global and national health service system, along with advances in digital technology that supports data integration among the service facilities. In Indonesia, the implementation of RME is directed at supporting interoperability among the health facilities through the Satu Sehat platform, as mandated by Regulation of the Minister of Health Number 24 of 2022. The research aims to evaluate the implementation of EMR in the Emergency Departement (ED) using the PIECES (Performance, Information, Economic, Control, Efficiency, and Service) approach. The method used is qualitative phenomenology, with data collection from interviews, observations and documentation studies. Research informants consisted of health workers, information technology staff and medical records officers. The research results show that the implementation of EMR in the ER has improved service performance, efficiency and quality of medical information. However, there are still obstacles such as a lack of information technology personnel, limited infrastructure and ongoing training that is not yet optimal. In conclusion, although the implementation of EMR in the ER at Bhayangkara Hospital has had a positive impact in supporting interoperability with Satu Sehat, improvements are still needed in terms of strengthening technological infrastructure and human resource training. This research recommends adding information technology experts, improving infrastructure to ensure data security, and ongoing training for EMR system. users to increase service effectiveness.